A Risk Management Framework for User-Generated Content on Public Display Systems. (3rd March 2019) - Coutinho, Pedro; José, Rui
Abstract : Digital public displays can represent a powerful medium for personal expression and situated communication. However, before they can actually serve as an effective communication medium, they need to move towards more open models, in which user-generated content can play a more prominent role in their relevance and value proposition. The key challenge, however, is how to share control with users while being able to guarantee that published content matches the social expectations of a place and the goals of the display owner. In this study, we explore a risk management methodology as a comprehensive approach to this issue. We propose a framework that supports the systematic elicitation of the risks involved, their prioritisation, and the selection of the specific combination of moderation techniques that is able to reduce risk to a level that is deemed acceptable, while minimising the moderation effort and the impact on the willingness of users to publish their content. With this overall framework, we expect to help display owners to reason about the moderation needs of their displays and the best mapping between those needs and various moderation techniques.